The internationalisation of Malaysian SMEs - Nik Abdullah, Nik Ab. Halim; Mohd Zain, Shahrul Nizam (2011)
This paper presents the descriptive analysis of a study on internationalisation among Malaysian SMEs.The objective is to highlight the number of firms that do involve in international market, reason for internationalisation and their mode of entry into foreign market.For SMEs that do not internationalise, the concern is more towards the reason why they did not.Discussions are based on the related theories of internationalisation namely the Uppsala Model, Network Approach and International New Venture or Born global.Data were collected through self-administered questionnaire and a total of 250 responds were received. Findings indicate that exporting was the most used mode of entry and increasing profit was the main reason for internationalisation.Various internationalisation processes were adopted but the step-by-step and cautious approach seems to be the most popular.Potential difficulties and uncertainties in making profit appear to be the major reason for SMEs that did not internationalise.Crosstab analysis has been conducted to look at the characteristics of SMEs that internationalise.Discussions of the findings, significance of the study and direction for future research are then discussed.